THE PARADOX OF ISLAMIC EDUCATION IN INDONESIA - Choirul Mahfud (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
Discussing today's Islamic education in Indonesia can be seen from an optic of politics of curriculum and policy in the politics of education. As we know that the reality of replacing the minister is always followed by replacing policy. Here, indeed, many people do not mean allergy or anti-change as long as the changes are still in the context of continuity and toward the better or the best. So, maybe no worries for all. In this paper, the focus of discussion is focused on important and interesting questions about how is the portrait of Islamic education in Indonesia? How the goals and the Quo Vadis of curriculum policy of Islamic education in Indonesia? How idealism education policy widely in Indonesia? How are the challenges and solutions for Islamic education problems in Indonesia? The paper is written by using qualitative data which is based on references and books literature, newsletters, journals and opinions in the mass media and other sources that are relevant in the study of Islamic education in Indonesia, particularly related to curriculum and education policy. The results showed that: first, a portrait of Islamic education in Indonesia from pre-independence to the independence of Indonesia continues to date indicating a paradox, besides the significant development and progress. Second, the goals of the policy of the Islamic education curriculum in Indonesia are always influenced by government policies at the same general education policy. How idealism education policy widely in Indonesia is the mainstreaming of education as a commander (education is king). Moreover, education policy is not merely to discuss the practice of education and learning, more than that is also concerned with the development of education in the competition at the same time the international synergies. Fourth, the challenges and solutions of Islamic education problems in Indonesia can be seen in terms of internal and external context. The solutions are about the culture of competitiveness balanced with the cooperation with all stakeholders need to be done for the goodness and the nation's welfare.Keywords: Islamic Education, Politics of Curriculum and Policy in Educational PoliticsAbstrakMembahas pendidikan Islam saat ini di Indonesia dapat dilihat dari optik politik kurikulum dan kebijakan dalam politik pendidikan. Seperti kita ketahui bahwa realitas penggantian menteri selalu diikuti dengan penggantian kebijakan. Di sini, memang, banyak orang tidak bermaksud alergi atau anti-perubahan asalkan perubahan masih dalam konteks kontinuitas dan menuju yang lebih baik atau yang terbaik. Dalam tulisan ini, fokus diskusi difokuskan pada pertanyaan-pertanyaan penting dan menarik tentang bagaimana potret paradoks pendidikan Islam di Indonesia? Bagaimana tujuan dan Quo Vadis tentang kebijakan kurikulum pendidikan Islam di Indonesia? Bagaimana idealisme kebijakan pendidikan secara luas di Indonesia? Bagaimana tantangan dan solusi untuk masalah pendidikan Islam di Indonesia? Makalah ini ditulis dengan menggunakan data kualitatif yang didasarkan pada referensi dan buku literatur, buletin, jurnal dan opini di media massa dan sumber-sumber lain yang relevan dalam studi pendidikan Islam di Indonesia, terutama yang berkaitan dengan paradoks pendidikan Islam. Hasil penelitian menunjukkan bahwa: pertama, potret pendidikan Islam di Indonesia dari pra-kemerdekaan hingga kemerdekaan Indonesia hingga saat ini menunjukkan paradoks, di samping perkembangan dan kemajuan yang signifikan. Kedua, tujuan kebijakan kurikulum pendidikan Islam di Indonesia selalu dipengaruhi oleh kebijakan pemerintah pada kebijakan pendidikan umum yang sama. Bagaimana idealisme kebijakan pendidikan secara luas di Indonesia adalah pengarusutamaan pendidikan sebagai panglima. Selain itu, kebijakan pendidikan tidak hanya membahas praktik pendidikan dan pembelajaran, lebih dari itu juga berkaitan dengan perkembangan pendidikan dalam kompetisi sekaligus sinergi internasional. Keempat, tantangan dan solusi masalah pendidikan Islam di Indonesia dapat dilihat dari segi konteks internal dan eksternal. Solusinya adalah tentang budaya daya saing yang seimbang dengan kerja sama dengan semua pemangku kepentingan yang perlu dilakukan untuk kebaikan dan kesejahteraan bangsa.Kata kunci: Pendidikan Islam, Politik Kurikulum dan Kebijakan dalam Politik Pendidikan